Religious Moderation In Islamic Portals: Study of mainstreaming religious moderation in the digital space - Tohari, Achmad; Mujlipah, Neneng (QISTINA: Jurnal Multidisiplin Indonesia, 2023)
The idea of religious moderation has existed since before the Ministry of Religion published a book on moderation initiated by Lukman Hakim, but after technological developments there have been changes in attitudes towards moderation, especially in the media with the many conservative narratives that build discourse about Islam which returns to the Sunnah and Al-Qur'an. -Qur'an. This research explains the discourse on religious moderation built by Islamic portals affiliated with Nahdlatul Ulama and Muhammadiyah, both of which have a long track record in voicing peaceful Islamic attitudes in Indonesia. The data in this research uses qualitative methods combined with literature review research on sources and journals that are still relevant to the research, then the analysis tool uses R. Entman's framing analysis. The findings achieved regarding the narrative discourse on religious moderation in the digital space on the Nu Online and Suaramuhammadiyah portals are that there is a desire for the formation of public understanding of the dangers of conservative Islam and the importance of understanding religious moderation more deeply in order to avoid the dangers of developing narratives. Both portals have a style its own framing in voicing and interpreting the discourse on the importance of a moderate attitude.